Risk-based decision making within strategic mine planning - Maybee, Bryan; Lowen, S.; Dunn, Paul (Inderscience Publishers, 2010)
Creating maximum value for shareholders within the underground mine planning process under varying economic and technical factors has become a reality. Due to the uncertainty and individual characteristics that define underground mining projects, each will exhibit its own individual risk profile, and thus cannot be evaluated based on historical information. This paper introduces a risk-based evaluation methodology that can be used to evaluate alternative mining strategies. The use of this methodology is illustrated through its application to a strategic level case study. Through this application it is shown that the inclusion of more information in the decision-making process can not only provide a more accurate valuation and allow for the recognition of risk, but can also alter the ultimate decision that is made.